1988
DOI: 10.1111/j.1600-0676.1988.tb01016.x
|View full text |Cite
|
Sign up to set email alerts
|

Estimate of prevalence of glucose intolerance in chronic liver disease. Degree of agreement among some diagnostic criteria

Abstract: ABSTRACT— In patients with chronic liver disease, the reliability of various criteria generally used to diagnose impaired glucose tolerance and diabetes was evaluated. Twenty‐one patients with chronic persistent hepatitis, 68 patients with chronic active hepatitis and 57 patients with liver cirrhosis were studied. All subjects underwent an oral glucose tolerance test (75 g). Impaired glucose tolerance and diabetes were diagnosed according to the criteria established by: the National Diabetes Study Group; Fajan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 9 publications
(2 reference statements)
0
12
0
Order By: Relevance
“…reported that, of 28 patients with chronic liver disease, 43% had normal glucose tolerance (NGT), 25% had impaired glucose tolerance (IGT) and 32% had DM at an oral glucose tolerance test (OGTT). Subsequent studies confirmed that abnormalities of glucose tolerance occur frequently in cirrhotic patients . In particular, Müller et al .…”
Section: Epidemiologymentioning
confidence: 77%
“…reported that, of 28 patients with chronic liver disease, 43% had normal glucose tolerance (NGT), 25% had impaired glucose tolerance (IGT) and 32% had DM at an oral glucose tolerance test (OGTT). Subsequent studies confirmed that abnormalities of glucose tolerance occur frequently in cirrhotic patients . In particular, Müller et al .…”
Section: Epidemiologymentioning
confidence: 77%
“…Alavian et al [12] in their study, however, reported a signifi cant association of diabetes with higher Child-Pugh score. Earlier, Buzzelli et al [15] had also reported a positive correlation between the prevalence of diabetes and/or IGT and severity of hepatic impairment.…”
Section: Discussionmentioning
confidence: 92%
“…[12] Kobashi et al [11] in their study from Mexico reported nearly 23% prevalence of type 2 diabetes among the CLD patients. Earlier, Buzzelli et al [15] had documented a high prevalence of both impaired glucose tolerance and diabetes in CLD.…”
Section: Discussionmentioning
confidence: 98%
“…Actually, the existence of the hepatogenous diabetes (HD) which developed as a complication of cirrhosis was suspected by Naunyn as early as in 1898 . From then on, many studies have demonstrated that IR and glucose intolerance were common in patients with early stages of chronic liver diseases . Diabetes manifests clinically as the liver function deteriorates; thus, the HD can be considered as a marker of advanced liver disease.…”
Section: Discussionmentioning
confidence: 99%